Decentralized Sampled-Data Control for Cyber-Physical Systems Subject to DoS Attacks - Li, Shi; Ahn, Choon Ki; Xiang, Zhengrong (IEEE systems journal, 2021)
To handle the global output feedback sampled-data (OFSD) control problem for cyber-physical systems (CPSs) described by nonstrict-feedback large-scale nonlinear systems with denial-of-service attacks, a decentralized OFSD control strategy is proposed. As only the system output is measurable at sampling instants when the investigated CPS works well and all states are unmeasurable when attacks occur, a novel mode-dependent state observer and a decentralized OFSD controller are designed according to the idea of the average dwell time method. It is proven that the resulting closed-loop system is globally asymptotically stable. The developed strategy is applied to practical systems to demonstrate its effectiveness.